SeleCTT: An Infrastructure for Selection of Concurrent Software Testing Techniques - Melo, Silvana M.; Moura, Felipe M.; Souza, Paulo S. L.; Souza, Simone R. S. (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2019: Anais do IV Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2019)
[Background]: A variety of software testing techniques have been published by the academia in the last years, however, the industry rarely embraces their use. The transference of knowledge between academia and industry is a challenge which is mainly occasioned by a lack of a solid base evidence with effective information to help the tester during the selection of a testing technique. [Aim]: This paper presents a computational infrastructure, called SeleCTT tool, that uses relevant information of concurrent software testing techniques to automate the selection of an adequate testing approach for a concurrent software project. [Method]: A review on the available technical literature was performed to identify attributes and concepts of concurrent software testing that affect the selection process and a characterization approach was developed and used as a kernel of the tool. [Results and Conclusions]: An online repository was built to guide the techniques selection, in order to provide interaction with the interested community. This works as a body of evidence for this area. Therefore, the SeleCTT tool provides a wide range access to all this information and also supports the decision-making process on the choice of the testing technique suitable for a concurrent software project.